Re-globalization new frontiers of political, economic, and social globalization - Benedikter, Roland 1965-; Gruber, Mirjam 1992-; Kofler, Ingrid (Routledge, 2022)
"Re-Globalization examines the changing face of globalization, with political, economic, and social balances in flux, and tensions increasing in many parts of the globe. This book discusses and problematizes the current transition phase of globalization - in response to issues such as inequalities, climate change, and health crises - offering a comprehensive collection of responses to the question "what is re-globalization?". The authors discuss the various definitions and forms of re-globalization, using a range of approaches, examples, and case studies in order to shed light on this process. The analysis of the phenomenon of re-globalization - understood as an economic, political, and social process - is both inter- and trans-disciplinary. This volume offers contributions from academic disciplines within the social sciences, as well as technology, global security, global studies, health, and climate and environmental sciences. Overall, the book analyzes and illustrates how globalization shifts are interconnected and how they relate to a transition in global society, proposing a framework for a series of future scenarios. This socio-geographically diverse book will be of great interest to students, scholars, and researchers across a broad spectrum of disciplines exploring the future of globalization"--
Aus der Introduction, Seite 2: "This volume is a result of the conference series "Understanding Globalization," which was held in May 2019 and May 2021 at the Center for Advanced Studies of Eurac Research, Bozen- Bolzano (Autonomous Province of South Tyrol, Italy)."
Keywords: Wirtschaftsentwicklung; Sozialer Wandel; Globalisierung; Konferenzschrift -- 2019 -- Bozen; Konferenzschrift -- 2021 -- Bozen